Laryngeal papillary carcinoma with unexpected evolution: case report - Fonseca, Adriano Santana; Chone, Carlos Takihiro; Crespo, Agrício Nubiato; Altemani, Albina (São Paulo Medical Journal, 2006)
CONTEXT: According to the literature, laryn- geal papillary carcinoma is rare and has a benign prognosis. CASE REPORT: In this report we present a sur- prising case with nodal metastasis at the time of diagnosis. Computed tomography showed infiltration of the lesion and metastatic lymph nodes. The resected specimen was submitted to histopathological study that confirmed the diag- nosis of papillary squamous cell carcinoma.